Tissue Differentiation by Refractive Index using Fiber Optic Displacement Sensor - Al-Ashwal, Rania; Ridhwan Sazali, Amirul; Lo Zhen Kai, Alex; Mustakim Ab Rashid, Amir; Hafiz Mohamad Afandi, Mohamad; Syafiq Mohd Najib, Muhammad; Afiqah Fadzil, Nurul; Mohamed Amin, Syakirah (International Journal of Engineering and Technology, 2018)
The optical properties can differentiate biological tissues. Refractive index (RI) is one of the optical parameters that can be used for the said purpose. Many different methods of measuring the refractive index of tissue have been found but involve complicated procedure and setup. The proposed way of measuring the refractive index of fabric using fibre optic displacement sensor does not include difficult steps. The installation has the highest measurement at 4 mm displacement between the fibre probe and the tissue sample. Sensitivity achieved when tested with three different solutions was 82.74 nW/RIU at the maximum movement. The installation can determine the refractive index of skin, muscle and fat tissue of porcine sample with a difference of 4.3%, 7.4% and 3.9% respectively using the standard RI of each tissue. The proposed method shows promising results and possible application of simple non-contact refractive index measurement of biological tissue.Â